The Architecture of Digital Deception: Mapping Fake News Typologies, Bot Behaviors, and Platform Vulnerabilities - Afansyah, Muhammad Fikri; Ahmad Nawi , Haslinda Sutan (International Journal of Advanced Science Computing and Engineering, 2025)
The emergence of social media has radically changed the nature of information production, dissemination, and consumption. Alongside its advantages, the diffusion of misinformation has become a major threat to debate, democratic processes, and social cohesion. The following paper presents an extensive review of typologies of fake news, drawing on existing scholarship that categorizes fake news as satire, propaganda, disinformation, misinformation, manipulation, rumor, crowdturfing, hate speech, spam, trolls, and cyberbullying. The two categories are discussed with respect to their purpose, precision, and influence on users. The role of bots and computational propaganda, which automate and amplify the spread of misleading content on the internet, particularly during sensitive periods when politics is salient, is also examined. The paper identifies several shortcomings of existing platform moderation systems, which largely fail to block the real-time dissemination of dangerous content. In a reaction, the paper highlights the important work of information professionals, i.e., journalists, teachers, educators, librarians, and specialists in digital media, being able to reduce the dissemination of false information. They are tasked with fact-checking, source validation, media literacy, and citizen empowerment in the assessment of online information. In addition, the paper promotes the development of more resilient AI-based detection mechanisms that can respond quickly to the proliferation of harmful content. Finally, the research is expected to foster a more aware and less vulnerable world, prepared to meet the challenges of the digital information era through technological devices and human knowledge.